Jargon Used by Teenagers in Social Media Snapchat: Jargon by Teenagers - Saleh, Eliza Farahdiba; Nur, Serliah; Emmiyati, Nuri (Journal of Islamic Culture and Literature (JICeL), 2024)
Snapchat has become one of the most popular social media platforms among teenagers, and its use is often accompanied by quirky terms or jargon. This study aims to examine the forms and functions of this jargon. The research method used is a qualitative approach by conducting observation participants where the researcher acts as a participant in the activity or situation being observed and used two theories; Halligan’s theory (2004) as a form of jargon suggests that the use of jargon in teenagers can reflect their efforts to convey their group identity and shows a sense of closeness in the Snapchat community and Jakobson’s theory (1960) as a language of function to analyze the terms of jargon in teenagers communication on the Snapchat. The data were obtained from Snapchat conversations that featured jargon. The researcher found 37 jargon items across ten accounts with an even split of five boys and five girls from various countries, Malaysia, Philippines, Indonesia, England, Norway, New York, United States, and Finland, with the identified users ranged in age from 18 to 24 years old. The jargon forms that the researcher has found were categorized into words (8), phrases (7), acronyms (5), and abbreviations (17), while the functions were identified as referential (9), poetic (1), conative (9), emotive (7), phatic (8), and metalingual (3). Keywords: Jargon, Snapchat, Social Media